Determination of Insurance Premiums to Mitigate the Risk of Company Losses Due to Supplier Failure Using Black-Scholes-Merton Model - Jessica Novia Sitepu; Betty Subartini; Sukono Sukono (Research Collaboration Community (RCC), 2023)
The Micro and Small Enterprises (MSMEs) sector in Indonesia has made a significant contribution to the Indonesian economy. However, MSMEs in Indonesia face various challenges that may occur in the future, for example, supplier failure. Therefore, it is essential to determine the right form of risk mitigation to reduce the impact of supplier failure for MSMEs, and one such approach is to have insurance. This study aims to calculate the premium price using the Black-Scholes-Merton model approach. The data used is the aggregate losses experienced by MSMEs fostered partners of PT Wijaya Karya (Persero) Tbk. Data simulation was generated on lognormal distribution to determine the premium price. The application of the Black-Scholes-Merton model on the calculations showed that MSMEs have to pay a premium of IDR 4.165.061 for one year.